ANALISIS DISPARITAS PENDAPATAN DAN POLA PERTUMBUHAN EKONOMI DI PROVINSI ACEH PERIODE 2002-2012 - ASRITA ZAHARA (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2015)
This research attempts to count disparity among of Regencies/Cities and to classify 23 the Regencies/Cities based on economic growth and GRDP per capita in Province of Aceh since 2002-2012. The data that used in this research consist of the GRDP at 2000 constant market price, economics growth and the number of population among of regencies/cities in Province of Aceh. Williamson Index, Entropy Theil Index and Klassen Typology, are tools of analysis. The Williamson disparity index and the Entropy Theil Index of the GRDP per capita among Regencies/Cities in Province of Aceh pointed number 0,375 and 1,455 of the average, and the index shows a decreasive tendency. Based on Klassen Typology show that: Regencies Aceh Besar, Bireuen, Bener Meriah, Banda Aceh, Sabang and Lhokseumawe are classified as high growth and high income. Regencies Aceh Selatan, Aceh Barat, Nagan Raya and Langsa are classified as high income but low growth. Regencies Simeulu, Aceh Singkil, Aceh Tenggara, Aceh Tengah, Pidie, Pidie Jaya, and Gayo Lues are classified as high growth but low income. Regencies Aceh Timur, Aceh Utara, Aceh Barat Daya, Aceh Tamiang, Aceh Jaya, and Subulussalam are classified as low growth and low income.